Pengembangan Media Pembelajaran Augmented Reality Materi Kerajaan Hindu Budha Untuk Meningkatkan Berpikir Kritis Siswa Kelas IV SD - Afifah, Awayna Faza; Zainuddin, Almuntaqo (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This study aims to provide changes to the Instagram Augmented Reality filter teaching media on Hindu Buddhist Kingdom material and determine student responses with a focus on improving the critical reasoning of class IV students at SD Muhammadiyah 1 Surakarta. This research uses the Research and Development (R&D) method with the ADDIE model. This media feasibility test is based on media experts and material experts through media and material expert validation sheets. Student responses with questionnaires and pre-test and post-test work to determine changes in students' critical reasoning. The results of the research stated that the Hindu Buddhist Kingdom learning media based on Instagram AR filters obtained a percentage score of 86.25% by media experts, 84.61% by material experts, and 98.84% by practitioners as material experts. Based on the Likert scale, the percentage scores are both included in the "very suitable" category for use in learning. The results of student responses to this media obtained a percentage score of 88.91% in the "valid" category. The results of the pre-test and post-test scores were obtained using the normality test and the Mann-Whitney U test, with the results showing a significant difference in students' critical thinking before and after using learning media.